2022
DOI: 10.1002/14651858.cd015017.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Ivermectin for preventing and treating COVID-19

Abstract: Background Ivermectin, an antiparasitic agent, inhibits the replication of viruses in vitro. The molecular hypothesis of ivermectin's antiviral mode of action suggests an inhibitory effect on severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) replication in early stages of infection. Currently, evidence on ivermectin for prevention of SARS‐CoV‐2 infection and COVID‐19 treatment is conflicting. Objectives To assess the efficacy and safety of ivermectin plus sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 109 publications
1
22
0
Order By: Relevance
“…A recent double‐blind, randomized, placebo‐controlled, adaptive platform trial involving >3000 symptomatic SARS‐CoV‐2–positive adults receiving either placebo or a relatively high dose (.4 mg/kg) of ivermectin once daily for 3 days did not result in a lower incidence of medical admission to a hospital due to progression of COVID‐19 in the ivermectin‐treated patients 117 . Several other randomized clinical trials and recent meta‐analyses showed similar findings 118,119 . Notwithstanding these findings, ivermectin is widely prescribed for COVID‐19 and is often used at high doses that may cause toxicity.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A recent double‐blind, randomized, placebo‐controlled, adaptive platform trial involving >3000 symptomatic SARS‐CoV‐2–positive adults receiving either placebo or a relatively high dose (.4 mg/kg) of ivermectin once daily for 3 days did not result in a lower incidence of medical admission to a hospital due to progression of COVID‐19 in the ivermectin‐treated patients 117 . Several other randomized clinical trials and recent meta‐analyses showed similar findings 118,119 . Notwithstanding these findings, ivermectin is widely prescribed for COVID‐19 and is often used at high doses that may cause toxicity.…”
Section: Discussionmentioning
confidence: 89%
“…117 Several other randomized clinical trials and recent meta-analyses showed similar findings. 118,119 Notwithstanding these findings, ivermectin is widely prescribed for COVID-19 and is often used at high doses that may cause toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Given that many of the suggested anti-COVID-19 drug agents are activated/metabolized by CYP3A4, this highlights the importance of studying the drug interactions related to vitamin D [ 202 ]. Ivermectin, for instance, has been suggested to have antiviral effect against COVID-19 and is metabolized via CYP3A4, hence a 2 h delay between the administration of ivermectin and vitamin D has been advised [ 203 ]. Another medication suggested in COVID-19 therapy due its anti-inflammatory effects is colchicine [ 204 ].…”
Section: Drug–drug Interactions Of Fat-soluble Vitamins and Covid-19 ...mentioning
confidence: 99%
“…Since 2015 Cochrane and other journal publishers have been exploring the publication of LSRs using different updating and publishing approaches 5. Having been involved in the production of several LSRs on COVID-19 for Cochrane, we used an approach adopted by many other author teams, which consists of running searches and screening results on a regular basis and publishing an updated version of the review as new evidence is identified 6 7. However, details of the ongoing surveillance between published LSR updates are not reported, leaving readers in the dark about whether the review is up to date and which new underpinning evidence, for example, relevant new studies, has become available since the last publication.…”
Section: Introductionmentioning
confidence: 99%